Greenland Melt and the Atlantic Meridional Overturning Circulation - Eleanor Frajka-Williams (Oceanography, 2016)
More than a decade of observations of the meridional overturning circulation in the subtropical North Atlantic show it to be highly variable on time scales of days to years and with an overall trend toward slowing down. Over the same time period, melting from Greenland (and elsewhere in the Arctic, including from sea ice) has been increasing, resulting in greater freshwater input to the northern North Atlantic. In this article, we examine evidence for the impact, if any, of this influx of freshwater on the large-scale ocean circulation and for potential changes.